ASSESSMENT OF THE CURRENT STATUS OF THE POPULATIONS OF TROLLIUS DSCHUNGARICUS REGEL IN THE FLORA OF THE KETPEN RIDGE OF THE KUNGEY ALATAU (Eurasian Journal of Ecology, 2025)
The article is dedicated to the study of the current status of two populations of Trollius dschungaricus Regel found in the flora of the Ketpen Gorge of the Kungey Alatau. The work presents a taxonomic, ecological, and geographical analysis of the floristic composition of these populations.The floristic composition of the T. dschungaricus populations includes 73 plant species belonging to 61 genera and 25 families. The largest number of species is represented by the families Poaceae  with 15 species, Asteraceae  with 14 species, Chenopodiaceae with 9 species, Fabaceae with 7 species, Lamiaceae with 4 species, Rosaceae with 3 species, as well as Ranunculaceae and Berberidaceae with 2 species each. The remaining families are represented by one species.An analysis of the age structure of the T. dschungaricus populations in Ketpen Gorge showed their stable condition, with a predominance of virginile and generative plants. The proportion of seedlings in the studied populations is relatively small, ranging from 2 to 9%. In both populations, generative individuals dominate, while immature plants are represented in small percentages. This is due to insufficient seed regeneration in recent years and the rapid transition of immature plants to the virginile stage. At the same time, there are no old, senile plants in the populations.The viability of T. dschungaricus individuals in the populations is primarily influenced by the type of habitat. The studied age structure indicates the good condition of populations living in the mountain meadows and mixed herbaceous phytocenoses of the Ketpen Ridge of the Kungey Alatau.Keywords: Trollius dschungaricus, population, Ketpen Ridge, age structure, floristic composition